Hubungan Tingkat Spiritualitas dengan Academic Burnout pada Mahasiswa Akhir Fakultas Keperawatan Universitas Riau - Putri, Dinda Daisya; Yuniar Sari, Niken; Novayelinda, Riri (NHM PRESS, 2023)
Academic burnout is the condition in which an individual feels physically, mentally, and emotionally tired due to work done over a long period time. Final year nursing student of Faculty of Nursing are at risk of experiencing academic burnout due to the many routines and tasks performed during the course. One factor that can affect academic burnout is the spiritual level. Method: The method in this study uses a descriptive design of correlation with the total sample of 142 respondents taken based on the inclusion criteria with total sampling techniques. The measurement tool used is the Maslach Burnout Inventory-Student Survey questionnaire which has passed the validity test with a count r value starting from 0.332-0.724 and Cronbach's alpha value of 0.895 and the Daily Spiritual Experience Scale which has passed validity tests with a table r value of 0.514 and r count of 0.804-0.874. The majority of respondents are aged 22 (55.6%), the majority are female (89.4%), and they are moslem (88.7%). A high spiritual level with a total of 59.2%. Academic burnout was 74.6 percent. The results of the statistical test chi-square obtained p-value = 0.536 (p>0.05). Conclusion: There was no link between the spiritual level and academic burnout in the final students of the University of Riau Faculty of Nursing.